2016
DOI: 10.1104/pp.16.00343
|View full text |Cite
|
Sign up to set email alerts
|

SPINDLY inhibits class I TCP proteolysis to promote sensitivity to cytokinin

Abstract: Arabidopsis (Arabidopsis thaliana) SPINDLY (SPY) is a putative serine and threonine O-linked N-acetylglucosamine transferase (OGT). While SPY has been shown to suppress gibberellin signaling and to promote cytokinin (CK) responses, its catalytic OGT activity was never demonstrated and its effect on protein fate is not known. We previously showed that SPY interacts physically and functionally with TCP14 and TCP15 to promote CK responses. Here, we aimed to identify how SPY regulates TCP14/15 activities and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 61 publications
1
56
0
Order By: Relevance
“…We examined transgenic tomato expressing the GUS reporter gene under the regulation of the synthetic CK-induced promoter TCS v2. TCSv2 harbors the concatemerized type-B RR-binding motifs (Steiner et al , 2016). Guard cells of the transgenic plants exhibited strong GUS activity following BA treatment (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined transgenic tomato expressing the GUS reporter gene under the regulation of the synthetic CK-induced promoter TCS v2. TCSv2 harbors the concatemerized type-B RR-binding motifs (Steiner et al , 2016). Guard cells of the transgenic plants exhibited strong GUS activity following BA treatment (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence of the synthetic promoter Two-Component Signaling Sensor ( TCS ) version 2 (Steiner et al , 2016) was ligated to the β-galactosidase (GUS) gene from Escherichia coli to generate a TCSv2:GUS fusion in pART27. This construct was introduced into Agrobacterium tumefaciens and then transferred to M82 cotyledons using the transformation and regeneration methods described by McCormick (1991).…”
Section: Methodsmentioning
confidence: 99%
“…1G). To determine whether the SAMs of the pin-like shoots retained their function, we monitored the expression of the two-component sensor (TCS) that marks cytokinin signaling (10). In WT, this reporter is expressed in the SAM proper, is excluded from the outermost two cell layers, and is weakly expressed in young leaf primordia (Fig.…”
Section: Significancementioning
confidence: 99%
“…To further examine whether CK dynamics could be altered by CLAU, we compared the expression of a CK activity reporter TCS fused to VENUS (Zürcher et al, 2013;Steiner et al, 2016) between wild-type tomato plants and the clau mutant ( Figure 6). We first confirmed that TCS is CK responsive in tomato as was reported in Arabidopsis (Supplemental Figure 4).…”
Section: Expression Of the Ck-response Reporter Tcs Is Upregulated Inmentioning
confidence: 99%
“…Tomato (M82, sp) plants expressing pFIL>>IPT and pFIL>>CKX were generated by the LhG4 transactivation system (Moore et al, 1998) and described previously (Shani et al, 2010). Tomato plants overexpressing TCSv2:3XVENUS were obtained from the Muller, Eshed, and Weiss labs (Steiner et al, 2016;Zürcher et al, 2013), confirmed to be CK responsive in tomato, and backcrossed into a clau background.…”
Section: Plant Materialsmentioning
confidence: 99%